2013
DOI: 10.2166/wst.2013.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wastewater chlorination on endocrine disruptor removal

Abstract: Endocrine disrupting chemicals (EDCs) are compounds of mainly anthropogenic origin that interfere with the endocrine system of animals and humans thus causing a series of disorders. Wastewater treatment plants are one of the major routes for transporting such chemicals to the water courses. In the context of this study, several chlorination batch tests were performed in order to assess the effectiveness of chlorination to remove bisphenol A (BPA), triclosan (TCS), nonylphenol (NP) and its ethoxylates (NP1EO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Several processes have been proposed to remove those micropollutants such as UV/TiO 2 photocatalysis [7,10], membrane bioreactor [11], chemical oxidation [12], chlorination [9,13], ozonisation [12,14], and activated carbon adsorption [14][15]. Amongst those processes, adsorption shows a promising prospect in removal efficiency and cost feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…Several processes have been proposed to remove those micropollutants such as UV/TiO 2 photocatalysis [7,10], membrane bioreactor [11], chemical oxidation [12], chlorination [9,13], ozonisation [12,14], and activated carbon adsorption [14][15]. Amongst those processes, adsorption shows a promising prospect in removal efficiency and cost feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these degradation products are far more toxic and biopersistant than the parent TCS. For example, Noutsopoulos et al [97] found 92% TCS removal at a free chlorine dose of 40 mg Cl 2 /L and at a contact time of less than 5 min, but observed a 50-to 100-fold increase in Vibrio fischeri toxicity compared to TCS prior to chlorination. Multiple TCS-containing personal care products have also been shown to react with free chlorine to form higher-chlorinated TCS intermediates, including dichloro-2-(2,3-dichlorohenoxy)phenol and trichloro-2-(2,3-dichlorohenoxy)phenol.…”
Section: Transformation/degradation Products and Metabolites Of Triclmentioning
confidence: 99%
“…Chlorination was questioned as a potential treatment technology for the EDCs BPA, triclosan, and NP from secondary wastewater effluent, and was not found to be completely effective (Noutsopoulos et al, 2013). NP, BPA, and triclosan were effectively removed (60-84%) at moderate chlorine doses, however, ethoxylates of NP (NP1EO and NP2EO) showed removal efficiencies of <37%.…”
Section: Chlorination Bromination and Chloraminationmentioning
confidence: 99%